Ecological, socio-economic and demographic analyses as prerequisites for sewage treatment problem solutions in rural areas. The case study of Dirlammen, Vogelsberg, Germany - Opp, Christian; Ziebolz, Bastian; Groll, Michael (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
The municipal sewage treatment in Germany is traditionally centralized and allows for a high disposal security. The implementation of the EU Water Framework Directive (EU-WFD) showed that the central target, the so-called ‘good ecological state’ has not yet been reached in 90% of all surface water bodies. A common and widespread measure to reach said target is the improvement of sewage treatment plants (STP). A large part of the expenses for that has to be shouldered by local communities. But many rural communities already have to manage high costs caused by the modernization of the sewage pipe system. And as the size of the rural population decreases continuously, the per capita burden increases. This raises the question whether the construction of a new sewage treatment plant is the most efficient way to improve the water quality in rural areas. A comprehensive approach has been developed for answering this question, consisting of 1) biological and physico-chemical wastewater analyses, 2) a modified eco-balance for the construction of a new STP and 3) socio-economic and demographic population analyses. The results show that the water quality of the studied creek is good with exception of the sewage disposal point. The eco-balance for the construction, the operation, and the environmental side effects show that the continued operation of the existing STP is more effective than the construction of a modern facility. This conclusion is supported by the aging and general decrease of the rural population. The diminishing potential to shoulder additional costs is in contrast to the reduced future demand for a modern STP.